Map the future of design for enhanced customer experience - Prahalad, Deepa 1972- (FTPress Delivers, 2011)
"This Element is an excerpt from Predictable Magic: Unleash the Power of Design Strategy to Transform Your Business (ISBN: 9780137023486) by Deepa Prahalad and Ravi Sawhney. Use "experience mapping" to create products, services, and experiences your customers will be truly passionate about!"--Resource description page.
Includes bibliographical references. - Resource description page (viewed Jan. 5, 2011)
Keywords: Strategic planning; Technological innovations; Competition; Customer relations; Planification stratégique; Innovations